2019
DOI: 10.1177/0300985819844822
|View full text |Cite
|
Sign up to set email alerts
|

Hyaline Arteriolosclerosis in 30 Strains of Aged Inbred Mice

Abstract: During a screen for vascular phenotypes in aged laboratory mice, a unique discrete phenotype of hyaline arteriolosclerosis of the intertubular arteries and arterioles of the testes was identified in several inbred strains. Lesions were limited to the testes, and did not occur as part of any renal, systemic, or pulmonary arteriopathy or vasculitis phenotype. There was no evidence of systemic or pulmonary hypertension, and lesions did not occur in female ovaries. Frequency was highest in males of the SM/J (27/30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 32 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…The presence of collagen has previously been described in hyaline arteriolosclerosis of intertubular arteries and arterioles in the testes of mice using Masson trichrome staining. 27 An increase in collagen type III and IV was also found in hyalinized glomeruli of patients with hypertensive nephrosclerosis through immunohistochemical staining and in situ hybridization. 42 Our results confirmed the crucial role of collagen in hyaline arteriolosclerosis and demonstrated its presence in the media of affected arterioles of hypertensive ischaemic skin ulcers and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The presence of collagen has previously been described in hyaline arteriolosclerosis of intertubular arteries and arterioles in the testes of mice using Masson trichrome staining. 27 An increase in collagen type III and IV was also found in hyalinized glomeruli of patients with hypertensive nephrosclerosis through immunohistochemical staining and in situ hybridization. 42 Our results confirmed the crucial role of collagen in hyaline arteriolosclerosis and demonstrated its presence in the media of affected arterioles of hypertensive ischaemic skin ulcers and hypertensive nephropathy.…”
Section: Discussionmentioning
confidence: 98%
“…8,9,11,14,40,41 Although several authors have previously reported on these hyaline wall changes, which can typically be found in the media of arterioles and small arteries, 9,20,28 few attempts have been made to characterize these deposits. 27 We introduced Raman imaging as an important tool to reveal molecular changes at the micron level within the vascular wall and hyaline deposits. Our data analysis showed that subendothelial hyaline deposits were mainly composed of collagen and phospholipids, particularly phosphatidylcholine.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations